Socialization of a Causalitic Learning Video Model Integrated with Traditional Gendang Beleq Music as an Effort to Strengthen Local Wisdom in Schools - Galuh Elisa Roliana Fatimah (Balai Publikasi Indonesia, 2026)
Science learning in junior high schools is often considered difficult and boring due to the memorization-heavy material and complex mathematical formulas, along with a lack of relevance to daily life. To address this, the causalitic learning model, which focuses on qualitative cause-and-effect analysis of natural phenomena, can be applied. Integrating this model with local wisdom, such as traditional Gendang Beleq music, offers a more engaging and contextual learning experience. This community service project aimed to socialize a causalitic learning video integrated with Gendang Beleq to strengthen local wisdom and improve students' understanding at SMPN 3 Labuapi. Survey results showed the video was highly suitable for use, with average scores of 87.8% from students and 96.4% from teachers, both in the